Feasibility of a Humor Training to Promote Humor and Decrease Stress in a Subclinical Sample: A Single-Arm Pilot Study - Tagalidou, Nektaria; Loderer, Viola; Distlberger, Eva; Laireiter, Anton-Rupert (Frontiers in Psychology, 2018)
The present study investigates feasibility of a humor training for a subclinical sample suffering from increased stress, depressiveness, or anxiety. Based on diagnostic interviews, 35 people were invited to participate in a seven-week humor training. Evaluation measures were filled in prior training, after training, and at a one-month follow-up including humor related outcomes (coping humor and cheerfulness) and mental health related outcomes (perceived stress, depressiveness, anxiety, and well-being). Outcomes were analyzed using repeated-measures ANOVAs. Within-group comparisons of intention-to-treat analysis showed main effects of time with large effect sizes on all outcomes. Post hoc tests showed medium to large effect sizes on all outcomes from pre to post and results remained stable until follow-up. Satisfaction with the training was high, attrition rate low (17.1%), and participants would highly recommend the training. Summarizing the results, the pilot study showed promising effects for people suffering from subclinical symptoms. All outcomes were positively influenced and showed stability over time. Humor trainings could be integrated more into mental health care as an innovative program to reduce stress whilst promoting also positive emotions. However as this study was a single-arm pilot study, further research (including also randomized controlled trials) is still needed to evaluate the effects more profound.